ANALISIS METACOGNITIVE BLINDNESS SISWA DALAM MENYELESAIKAN MASALAH BERBASIS HIGHER ORDER THINKING SKILL - Bernadetha Silaban; Darhim Darhim (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2023)
This study aims to trace the process of occurrence of metacognitive blindness in students in solving HOTS-based problems. This type of research uses qualitative methods. Data collection techniques used test instruments in the form of HOTS-based problem-solving questions and interviews. The sampling technique in this study uses Purposefully selection, where the researcher chooses deliberately and fully planning the participants to be studied. The results showed that both subjects experienced metacognitive failure caused by a presence flag during the problem-solving process. S1 experienced metacognitive blindness namely 1) errors in understanding what is meant by the problem, 2) being unable to connect one understanding with another understanding, 3) maintaining an inappropriate strategy, and 4) ignoring correct calculations when planning solutions and implementing plans. Furthermore, Subject S2 experienced metacognitive blindness namely 1) students maintain inappropriate mathematical problem-solving strategies, 2) are unable to relate one understanding to another, and 3) maintain inappropriate strategies.